2011
DOI: 10.1117/1.3658757
|View full text |Cite
|
Sign up to set email alerts
|

Role of the prefrontal cortex in the cognitive control of reaching movements: near-infrared spectroscopy study

Abstract: Abstract.To elucidate the role of the prefrontal cortex in cognitive control of reaching movements, by multichannel near-infrared spectroscopy we examine changes in oxygenated hemoglobin (oxy-Hb) as an indicator of changes in regional cerebral blood flow in the bilateral dorsolateral (DLPFC), ventrolateral prefrontal cortex (VLPFC), and frontopolar cortex (FPC) during a reaching task with normal visual feedback (a consistent task) and a reaching task with flipped horizontal visual feedback (an inconsistent tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…During reaching movements with visuomotor rotation, the bilateral dorsolateral prefrontal cortex showed higher activity in the initial learning phase that gradually decreased in parallel with improved motor performance as the trial proceeded (Goto et al, 2011). During reaching movements with visuomotor rotation, the bilateral dorsolateral prefrontal cortex showed higher activity in the initial learning phase that gradually decreased in parallel with improved motor performance as the trial proceeded (Goto et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During reaching movements with visuomotor rotation, the bilateral dorsolateral prefrontal cortex showed higher activity in the initial learning phase that gradually decreased in parallel with improved motor performance as the trial proceeded (Goto et al, 2011). During reaching movements with visuomotor rotation, the bilateral dorsolateral prefrontal cortex showed higher activity in the initial learning phase that gradually decreased in parallel with improved motor performance as the trial proceeded (Goto et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…This variation in neural activity depending on motor performance is not limited to motor-related areas. During reaching movements with visuomotor rotation, the bilateral dorsolateral prefrontal cortex showed higher activity in the initial learning phase that gradually decreased in parallel with improved motor performance as the trial proceeded (Goto et al, 2011). Therefore, the acquisition of neural processing efficiency not only in the motor-related areas but also in the frontoparietal network is likely necessary for improved motor performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the DLPFC plays an important role in top-down attention control and in executive functions, such as planning and problem-solving 2834 . In motor-learning, DLPFC activity is related to cognitive control of sensory input and future action planning in the fast motor-learning stage 35,36 , as well as in the encoding of declarative memory 37,38 . A meta-analysis of neuroimaging studies on motor-learning divided motor training periods into three phases, including short-term (≤1 h), medium-term (>1 h and ≤24 h), and long-term (24 h to <5 weeks) periods 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The motor cortex of the frontal lobes is involved in the planning and execution of movement, such as walking and reaching, but more anterior frontal areas are associated with reaching as well. Using near-infrared spectroscopy with adults, Goto et al (2011) reported that the lateral prefrontal cortex was involved in reaching that was both perceptually consistent and perceptually effortful. Wallis et al (2001) demonstrated that monkeys with lesions to the lateral prefrontal cortex had difficulty transferring reaching strategy to a new context.…”
Section: Introductionmentioning
confidence: 99%